Strategies to recover biological products using solid adsorbents: from polymeric resin beads to the development of novel 3D printed materials - Galindo Rodríguez, Giuseppe Rafael (The University of Edinburgh, 2023)
In the present work, different strategies were used to recover taxadiene from culture media using solid adsorbents. Taxadiene was produced in microbial cultivations using Saccharomyces cerevisiae strain LSR5 as biocatalyst. In a previous study, Santoyo-Garcia et al. used Diaion HP-20 to recover taxadiene from S. cerevisiae LRS5 cultivations. They recovered around 50% of the total taxadiene using a resin concentration of 3% (w/v) and observed cell growth inhibiting using higher concentrations (6 and 12% w/v). In chapter 3, an expanded bed adsorption column was set up to in situ recover taxadiene using Diaion HP-20 from culture media. Taxadiene titres and partition using the expanded bed adsorption column were compared with cultivations using Diaion HP-20 dispersed in the bioreactor vessel. The cultivations with the two bioreactor configurations were carried out using two adsorbent concentrations, 3 and 12% (w/v). Stirring speed at 800 rpm inhibited cell growth in the cultivation with dispersed resin using 12% adsorbent concentration, while cell growth was achieved in the same cultivation after reducing the stirring speed to 100 rpm. This result suggested that cell growth inhibition with large resin concentration was attributed to shear stress on the cells rather than the undesired adsorption of nutrients and substrates that reduce their availability in the culture media. Higher taxadiene titres were obtained in cultivations with 3% concentration of Diaion HP-20. The cultivations with dispersed resin showed higher taxadiene titres compared to the expanded bed adsorption column no matter the adsorbent concentration used. On the other hand, taxadiene partition (i.e. percentage of taxadiene capture by the resin from total taxadiene) was improved in the cultivations with 12% Diaion HP-20. In chapter 4, the approach to recover taxadiene switched to the development of 3D printed materials that can be used as solid adsorbents. The 3D printed materials were fabricated by photopolymerisation in a digital light processing printer. Two photopolymer resins were developed using limonene (LIMO) and benzyl methacrylate (BEMA) as main monomers to fabricate hydrophobic materials suitable for taxadiene adsorption. Schoen gyroids were successfully fabricated with the two resins up to a resolution of 250 μm, displaying a sharp pattern. The adsorption capacity of the 3D printed materials were tested in batch adsorption experiments using Sudan 1 as a model hydrophobic solute. BEMA material showed higher adsorption capacity for Sudan 1 and was selected for further studies. In chapter 5, porogen content was adjusted in the resin composition to fabricate materials with different pore structure and assess their adsorption capacity for Sudan 1 and Paclitaxel. Pore size distribution and average pore size on the different materials was estimated from SEM images. The analysis revealed that decreasing the porogen content resulted in materials with smaller pores. The material with higher adsorption capacity was obtained using 40% (v/v) of porogen in the resin composition (BEMA40). The performance of BEMA40 to recover taxadiene was tested and compared to Diaion HP-20 in small-scale (5 mL) cultivations. Taxadiene titres on BEMA40 and Diaion HP-20 were 46 ± 2 and 55 ± 4, respectively. No taxadiene was detected in the cells and cell free media in these cultivations, suggesting that nearly 100% of the taxadiene partition was on the adsorbents. BEMA40 were tested at larger scale in a bioreactor setup where the 3D printed material was inserted inside the fermenter vessel. The biomass concentration from this cultivation and taxadiene titre were 5.9 and 6 fold lower compared to the small cultivations, respectively. The lower taxadiene was apparently correlated to the low biomass production. It seemed that the presence of the 3D printed adsorbent inside the vessel induced shear stress to the cells. The results of this work demonstrate the potential of 3D printing to fabricate adsorbent materials and their application in the recovery of biological products. An interesting aspect about 3D printing is the adjustment of material chemistry, pore structure and the possibility to fabricate objects with complex geometries, different shapes and dimension. All these possibilities makes 3D printing a very versatile technology that could be exploited in biotechnology.
Keywords: recover taxadiene; Saccharomyces cerevisiae strain LSR5; biocatalyst; Diaion HP-20; limonene; benzyl methacrylate; fabricated adsorbent materials; 3D printing